Determination of The Anti-Fungal Effort of Morganella Morganii and Determination of Its Chemical Composition by Means of Gas Chromatography Method - Mass Spectrometry Gas Chromatography-Mass Spectrometry (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The analysis of bioactive was done by used gas chromatography-mass spectroscopy(GC-MS) method then antifungal and antimicrobial activity for methanolic extract was measured in the lab. The analysis of  Morganella morganii  by GC-MS revealed the existence of the Tricyclo, 3-Methoxybenzaldehyde semicarbazone , undecan-1-amine, carboxaldehyde , 1-methyl-,oxime ,(Z)-(+), 4-(2,5-Dihydro-3-methoxyphenyl) butylamine , Paromomycin , 1,5,5-Trimethyl-6-methylene-cyclohexene, 9-Borabicyclo[3.31], Benzenemethanol , nonane , 9-mercapto-2-(2-aminopropoxy)-3-methyl, Acetamide , N-(6-acetylaminobenzothiazol-2-yl)-2-(adamantan, rin-6-carboxylic acid , N-(2,5-Dicyano-3,4-dihydro-2H-pyrrol-2-yl)- acetamide, 3,10-Dioxatricyclo4-(2,5-Dihydro-3-methoxyphenyl)butylamine, [4.3.1.0(2,4)] phenylmethyl ester, 3,7-Diazabicyclo dec-7-ene, 3-Cyclohex-3-enyl-propionic acid, Eicosanoic acid  [3.3.1] 9,9-dimethyl-, nonane ,Dithiocarbamate , dl-Homocysteine, 2-(2-Furyl)pyridine, S-methyl-,N-(2-methyl-3-oxobutyl)-, 1,7-Dioxa-10-thia-4,13-diazacyclopentadeca-5,9,12-trione, 5,7-Dodecadiyn-1,12-diol, 1-(β-d-Arabinofuranosyl)-4-O-difluoromethyluracil, Uric acid, Pyrrolo[1.2-a]pyrazine-1,4-dione , hexahydro-,12-Methyl-oxa-cyclododecan-2-one, Phthalic acid , butyl undecyl ester, 9,12,15-Octadecatrienoic acid , 2,3-bis(acetyloxy)propyl ester, , methyl ester, 12-Dimethylamino-10-oxododecanoic acid , 1,2,4-Trioxolane-2-octanoic acid 5-octyl-, Octahydrochromen-2-one, L-Aspartic acid, N-glycyl-,2H-Oxecin-2-one , 3,4,7,8,91,10-hexahydro-4-hydroxy-10-meth, Thiazolo[4,5-d]pyrimidine-5,7(4H,6H)-dione , 3,6,12-Trimethyl-1,4,7,10,13,16-hexaaza-cyclooctadecane, 2-lodohiistidine, 2-amino-4-(2-ph,Dec-9-en-6-oxo-1-ylamide,2,5-Piperazinedione,3,6-bis(2-ethylpropyl)-, 9-Octadecenamide , (Z)-, 3',8,8'-Trimethoxy-3-piperidyl-2,2'-binaphthalene-1,1',4,4'-tetra . Citrullus colocynthis (Crude) was very highly active (6.39±0.27) mm anti-fungal activity of Morganella morganii showed that unstable compounds ( volatile )were effective hight to decrease the growth of Aspergillus terreus (5.613±0.23). the production of Morganella morganii give many essential secondary metabolites with a lot of biological activities. in pharmacy we depend on the significance of using bioactive compounds to made drugs for many diseases as for treatment, compounds purification of which  produced by Morganella  morganii will  be benefit for use.